(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
At the first time the mode of endoinulase purification from dapple has been proposed. Endoinulase was released from Taraxacum officinale root cells, solved in water, settled at pH 6.2, then the sediment was treated by buthanol. The purification was obtained by gel-filtration method applying organic solvents (buthanol and acetone) as well as a column containing G-150 Sephadex (with 2.0×120 cm2 sizes). The enzyme was purified 71.3 times, its molecular mass was 176 kDa.